Feasibility of extracting valuable minerals from desalination concentrate: a comprehensive literature review. (1st August 2015) - Shahmansouri, Arash; Min, Joon; Jin, Liyan; Bellona, Christopher
Abstract: Desalination of unconventional water resources is becoming increasingly common for the augmentation of drinking water supplies. Desalination is energy and cost intensive, and concentrate disposal is a significant issue that impedes desalination in many regions of the globe. One possible approach to decrease desalination costs while alleviating concentrate disposal issues is through the extraction of valuable commodities. While past researchers have evaluated the technical feasibility of extracting minerals from both seawater and, to a lesser extent, desalination concentrate, the feasibility of commodity extraction is dependent upon technical, energy, and cost considerations, as well as, market fluctuations of the minerals extracted. Most of the available literature has focused on technical processes used to extract minerals and has not evaluated the feasibility of extraction considering the aforementioned concerns. For this study, the feasibility of material extraction from seawater and desalination concentrate was investigated through three steps: 1) screening for potentially profitable compounds; 2) reviewing literature on extraction methods and market fluctuations for these compounds; and 3) assessing the costs of extracting these compounds. Although the extraction of various compounds from desalination concentrate is technically viable, based on the literature review and the primarily cost analysis, the extraction of the majority would not be profitable considering the current market and available technologies. The results from this study suggest that while the extraction of commodities of sodium, chlorine, potassium, and magnesium from desalination concentrate could be profitable, the feasibility of extraction is highly dependent on commodity pricing and final product purity. Due to the marginally attractive economics of extraction and significant uncertainties associated with producing commodities, this study suggests that extraction from desalination concentrate is unlikely to significantly improve the economics of desalination unless concentrate disposal costs were significantly reduced as a result. Graphical abstract: Highlights: Extraction from desalination concentrate is dependent upon numerous factors. If high purity products could be produced, extraction of major ions is feasible. Extraction of trace metals is currently economically unfeasible.